2015
DOI: 10.1039/c4ra11658e
|View full text |Cite
|
Sign up to set email alerts
|

Defect driven ferromagnetism in SnO2: a combined study using density functional theory and positron annihilation spectroscopy

Abstract: Room temperature ferromagnetic ordering has been observed in high purity polycrystalline SnO 2 sample due to irradiation of 96 MeV oxygen ions. Ab initio calculation in the density functional theory indicates that tin vacancies are mainly responsible for inducing magnetic moment in SnO 2 whereas oxygen vacancies in SnO 2 do not contribute any magnetic moment. Positron annihilation spectroscopy has been employed to characterize the chemical identity of irradiation generated defects in SnO 2 .Results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 47 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…The green and yellow bands (Fit 3 and 4) have a considerable shi for ferromagnetic ZnO-480 and ZnO-960 samples than the diamagnetic ZnO-0 and ZnO-60. Now ball-milling process favors the formation of cationic vacancies 9,23 and our observations from Raman data support this. Hence the green emission (Fit 3) of these samples is attributed to the appearance of V Zn .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The green and yellow bands (Fit 3 and 4) have a considerable shi for ferromagnetic ZnO-480 and ZnO-960 samples than the diamagnetic ZnO-0 and ZnO-60. Now ball-milling process favors the formation of cationic vacancies 9,23 and our observations from Raman data support this. Hence the green emission (Fit 3) of these samples is attributed to the appearance of V Zn .…”
Section: Resultssupporting
confidence: 79%
“…There are also some reports where the observed moment exceeds the maximum possible spin moment per dopant cation or the dopant atoms are found to be paramagnetic where the sample as a whole is showing FM. 2,3 Interestingly studies have found FM even in undoped ZnO [4][5][6] and other undoped semiconducting oxides [7][8][9] prepared using different synthesis techniques and it is termed as d 0 FM. 10 The attractive properties of ZnO such as wide band gap and large excitonic binding energy ($3.37 eV and 60 meV respectively at RT), piezoelectricity, large electronegativity of O atom leading to strong p-d exchange between localized spins and carriers for DMSs; 11 make it the most studied oxide semiconductor in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is not limited to ZnO but has been found in highly disordered SnO2 and TiO2 (ref. 67) and other wide band gap semiconductors.…”
Section: Results Of Raman Spectroscopic Measurement Of the Samples Ha...mentioning
confidence: 99%
“…In last several years, a number of oxides e.g., ZnO, MgO, TiO 2 , BaTiO 3 etc., showed ferromagnetic behaviour even at room temperature with the formation of atomic defects. [29][30][31][32][33] Ab-initio calculations in the frame work of density functional theory (DFT) have nicely explained the origin of such unusual ferromagnetism. [34][35]…”
Section: Introductionmentioning
confidence: 99%